THE TRANSFORMATION OF TRADITIONAL MORAL VALUES AND THE ROLE OF SOCIAL MEDIA AND ARTIFICIAL INTELLIGENCE (Spectrum Journal of Innovation, Reforms and Development, 2025)
This article analyzes the transformation of traditional moral values, the significance of social media and artificial intelligence, based on modern approaches and theoretical views. It discusses the transformation of traditional moral values, the positive and negative consequences of social media, and the issues of the younger generation becoming addicted to attractive and diverse social networks and AI tools from a philosophical point of view.